Correlation Between Biochemical Oxygen Demand And Chemical Oxygen Demand, At High Salinity Bioreactor-Based, Wastewater Treatment Plant In Al-Hasa Saudi Arabia. - Majeb Alotaibi; Faris Munshi; Ashraf Refaat; Mohamed El Said; Mohd Nasir (Journal of Water, 2023)
This study aims to determine an empirical relationship between the biological and chemical oxygen demands of industrial effluent running through the membrane bio reactor-based Al-Hasa common industrial wastewater treatment Plant. The relationship between these two parameters was investigated over one month (NOV– 2021 to OCT-2022). The values of R² show that its impossible to predict the result of BOD5 based on COD, however the result of r in AUG month shows a strong relation between them. The average biodegradability index over the one year is less than 0.6, showing that effluent is highly polluted, and biodegradation will not proceed. The plant’s performance in terms of BOD5 and COD removal was very poor over the whole year, however, the months AUG, SEP and OCT months shows a satisfactory performance, this is because a large amount of Industrial wastewater entering the plant contains both organic and inorganic components.
Keywords: Membrane bioreactor